2012
DOI: 10.1007/s00192-011-1642-6
|View full text |Cite
|
Sign up to set email alerts
|

Does bladder wall thickness decrease when obstruction is resolved?

Abstract: If obstruction is resolved, bladder wall thickness decreases. Preoperatively elevated residual urine may increase the risk of persistent obstruction after urethrolysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 34 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…However, it is critical to identify reversible causes of these symptoms instead of just attempting to mask them with standard overactive bladder treatment regimens. Although rates vary in the literature, sling division/partial or complete removal for obstruction has been shown to resolve up to 86% to 97% of associated voiding dysfunction symptoms and 60% to 90% of associated overactive bladder symptoms . In contrast, Starkman et al found these symptoms refractory in more than 50% of women after successful urethrolysis.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is critical to identify reversible causes of these symptoms instead of just attempting to mask them with standard overactive bladder treatment regimens. Although rates vary in the literature, sling division/partial or complete removal for obstruction has been shown to resolve up to 86% to 97% of associated voiding dysfunction symptoms and 60% to 90% of associated overactive bladder symptoms . In contrast, Starkman et al found these symptoms refractory in more than 50% of women after successful urethrolysis.…”
Section: Discussionmentioning
confidence: 99%